Risk Factors for Progression of Distal Deep Vein Thrombosis - Fujioka, Shunichiro; Ohkubo, Hirotoki; Kitamura, Tadashi; Mishima, Toshiaki; Onishi, Yoshihiko; Tadokoro, Yuki; Araki, Haruna; Matsushiro, Takuya; Yakuwa, Kazuki; Miyamoto, Takashi; Torii, Shinzo; Miyaji, Kagami (Circulation Journal, 2020)
Background:There is insufficient evidence regarding the optimal treatment method for distal deep vein thrombosis (DVT), including indications for anticoagulation therapy. Treatment results of patients with distal DVT were evaluated to clarify the risk factors that result in extension of distal DVT to the proximal vein and indications for anticoagulation therapy.Methods and Results:Among 430 patients with DVT between January 2018 and December 2019, 253 were diagnosed with distal DVT; 41 patients who had already started anticoagulation therapy were excluded, and the remaining 212 were included as study subjects. Anticoagulation therapy was not started immediately; conservative treatment with compression stockings was performed. Ultrasonography after 2 weeks revealed thrombus disappearance in 39 patients (21%), and thrombus reduction in 38 patients (20%). In contrast, extension of thrombus to the proximal vein was noted in 12 patients (6.3%) and anticoagulation therapy was commenced. After 3 months, the thrombus had disappeared in 75 patients (52%). No patient developed pulmonary thromboembolism during follow-up. With respect to the risk factors for extension to proximal vein during conservative treatment, active cancer (P=0.03), prolonged bed rest (P<0.01), and D-dimer level >8µg/mL (P=0.01) were identified.Conclusions:It is reasonable to consider anticoagulation therapy in distal DVT patients with active cancer, prolonged bed rest or high D-dimer level.